2018
DOI: 10.1111/jam.14177
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Controlled Release of Microencasulated Hydrogen Peroxide for Wound Treatment Applications

Abstract: Aims Hydrogen peroxide (H2O2) disinfection applications are limited by its rapid inactivation. The aims of this study were to (i) micro‐encapsulate H2O2 in silica hydrogels to obtain controlled release up to 72 h, (ii) test hydrogel antimicrobial activity against four common pathogens and (iii) assess H2O2 release kinetics and antimicrobial activity in 35–65% relative humidity and 37°C to approximate bandaged wound conditions. Methods and Results Hydrogels were characterized using scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A slow release of H 2 O 2, at low concentrations, may prevent bacterial infections in wounds, and H 2 O 2 at low concentrations is more stable. In another study, a continuous and slow release of H 2 O 2 in diluted honey allowed the development of a hydrogel to achieve a continuous, controlled release of H 2 O 2 for up to 72 h [ 55 ]. Also, H 2 O 2 micro-encapsulated hydrogels demonstrated broad-spectrum antimicrobial activity with as little as 10 min of contact time [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A slow release of H 2 O 2, at low concentrations, may prevent bacterial infections in wounds, and H 2 O 2 at low concentrations is more stable. In another study, a continuous and slow release of H 2 O 2 in diluted honey allowed the development of a hydrogel to achieve a continuous, controlled release of H 2 O 2 for up to 72 h [ 55 ]. Also, H 2 O 2 micro-encapsulated hydrogels demonstrated broad-spectrum antimicrobial activity with as little as 10 min of contact time [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on several factors but mainly on its concentration, H 2 O 2 may exert either bacteriostatic or bactericidal effects. H 2 O 2 at low concentrations, that are more stable than higher concentrations, exerts weak antibacterial activity; however, extended slow-release of H 2 O 2 may improve its antibacterial activity and overwhelm the effect of bacterial/plant catalase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have suggested that polyphenols could be involved in the generation of hydrogen peroxide at low concentration by autoxidation of polyphenols ( Bucekova et al, 2019 , Grzesik et al, 2019 ), and the slow release of in honey may improve its antibacterial activity ( Dogan-Guner et al, 2018 ). A new finding documented a significant correlation between the and total phenol content in the overall antibacterial activity of the honey ( Grzesik et al, 2019 )…”
Section: Discussionmentioning
confidence: 99%